The Influence of Factors of Breastfeeding and Food Consumption on Stunting Incidence among Preschool Children in Keerom District, Papua Province, Indonesia - Ngardita, I. Rai; Sumardi, Ratih Nurani; Lusiana, Sanya Anda; Mataram, I. Komang Agusjaya; Yunianto, Andi Eka (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Stunting is a nutritional problem due to linear growth failure in children under five, resulting in future health problems. Papua has a prevalence of stunting in children under five of 17.8% in 2018. AIM: This study aimed to analyze the influence of breastfeeding and consumption factors on the incidence of stunting in Keerom District, Papua Province. METHOD: This study was an observational study with a cross-sectional design. The sample in this study was 324 toddlers. Characteristics data and breastfeeding were obtained by interviewing parents. In contrast, data on the consumption of children under five were obtained using the Food Recall. Nutritional status was calculated using the Z-score obtained from measurements of body weight and height of children under five. SEM analysis was used to analyze breastfeeding and consumption factors on children’s nutritional status under five. RESULT: The study results based on consumption (r = 0.052) and breastfeeding (r = -0.015) had a weak relationship with stunting incidence. CONCLUSION: There was a significant effect of consumption and breastfeeding factors on the incidence of under-five stunting.